Penggunaan Kecerdasan Buatan Dalam Perkembangan Hukum Ketenagakerjaan di Indonesia - Pratiwi, Marisa (RIO LAW JURNAL, 2025)
This study discusses the use of Artificuaal Intelligence in the development of labor law in Indonesia. The formulation of the problem is 1. What is the position of artificial intelligence in Indonesia's employment sector? 2. What is the legal relationship with companies that employ artificial intelligence as workers? The method used in this study is Normative Juridical. The discussion in this paper is 1. Legal Relationship Between Companies and Artificial Intelligence as Workers, 2. The responsibility of companies that employ artificial intelligence as a workforce. The conclusion in this paper is 1. that between humans and artificial intelligence only as a collaboration or artificial intelligence can be said to be a tool that helps humans to do work quickly with better results, 2. The Electronic Information and Transaction Law states that the implementation of artificial intelligence (AI) in Indonesia can only be carried out by people, state administrators, business entities, and the community. This means that legal accountability will be borne by the electronic system operator who provides artificial intelligence (AI) services. If artificial intelligence (AI) is analogized to a worker, then the issue of legal responsibility can be imposed on the owner who can be analogized as an employer.